O045 Sleep management strategies among medical students. (9th November 2022) - Duthie, C; Cameron, C; Smith-Han, K; Beckert, L; Delpachitra, S; Garland, S; Sparks, B; Wibowo, E
Abstract: Introduction: Medical students are undertaking an intense curriculum, the stress of which may cause or worsen insomnia and depressive symptoms. We aim to investigate factors which might affect the sleep of medical students, and how they currently manage their sleep. Methods: A brief online survey was sent to medical students, consisting of validated questionnaires, and questions related to sleep management strategies. Results: We recruited 828 participants—49.5% reported insomnia symptoms and 51.4% reported depressive symptoms. After adjusting for gender, ethnicity and age, depressive symptoms (Mild: odds ratio (OR) = 6.26; Moderate: OR = 18.13; Severe: OR = 15.57), and sleep hygiene (OR = 1.07) were associated with insomnia symptoms. Commonly endorsed strategies for sleep management by students were undertaking regular exercise (80.1%), having consistent sleep-wake time (71.3%), and limiting caffeine intake (70.3%). Few were willing to see a clinician (23.4%) or take medication (22.3%). Participants with insomnia symptoms were more likely to prefer limiting their alcohol intake (OR = 1.77), limiting daytime naps (OR = 1.5), seeing clinicians (OR = 1.86), and taking sleep medication (OR = 3.98), but less likely to prefer avoiding intense work (OR = 0.71) or minimizing using electronics (OR = 0.60) close to bedtime than those without insomnia symptoms. High sleep self-efficacy was associated with lower odds for having insomnia symptoms (OR = 0.74 (0.70, 0.77)). Discussion: Self-reported insomnia and depression are common among medical students. Increased awareness and greater resources are needed to support the sleep health and emotional well-being of medical students.